Arts teacher evaluation: How did we get here?. Issue 1 (2nd January 2016) - Shaw, Ryan D.
ABSTRACT: Arts educators recently have found themselves in unfamiliar and sometimes-frustrating situations regarding their performance evaluations. The push for value-added models, effectiveness ratings based on schoolwide test score averages, portfolios, student learning objectives, and other measures of teacher effectiveness has dramatically changed arts teachers' evaluation procedures. Without sufficient knowledge of relevant educational history, these changes may seem to have emerged out of thin air. This article offers brief histories of teacher evaluation practices and teacher effectiveness/quality research, and discusses how the two histories recently collided to shape policy. Lingering questions for arts teachers are examined. Finally, recommendations are offered for how arts teachers can proactively deal with current and evolving teacher evaluation policies.